A qualitative study exploring staff attitudes to maintaining hydration in neurosurgery patients. Issue 3 (6th May 2018) - Litchfield, Ian; Magill, Lisa; Flint, Graham
Abstract: Aims: To explore staff perceptions of the processes and influences on maintaining patients' hydration on a busy neurosurgery ward. Background: Dehydration continues to be a major concern in the NHS where its avoidance is hindered by complications arising from clinical conditions, poor assessment and documentation of hydration and a lack of staff time to monitor fluid intake. Recent work has explored patient perceptions of hydration care but there has been little conducted recently that has explored those of staff. Methods: Semi‐structured interviews were conducted with staff working on a neurosurgery ward during 2016. We used open‐ended questions to elicit experiences of hydration care and explore factors that influenced the maintenance of hydration in patients. Results: We found that staff were aware of the importance of hydration and saw it as a central aspect of the care they provided. A range of staff are involved in the assessment of patients' hydration requirements and their ability to meet them. Similarly all staff were expected to provide oral fluids for patients able to drink independently. Competing priorities inhibited the time staff could spend providing hydration care which had an impact on the timely and accurate completion of fluid balance charts and meant that relatives were relied on to support patients requiring assistance in drinking.